Social Dilemmas in Environmental Economics and Policy Considerations: A Review - Cerutti, Nicola (ETHICS IN PROGRESS, 2017)
Many crucial environmental issues lead to social dilemmas, in which the personally optimal solution, and the socially optimal solution diverge. Finding a solution to this dilemma is extremely important to allow a good and sustainable management of many exhaustible natural resources. This is especially true when the resource users need to develop collectively a set of rules or practices, and the institutions are unable to provide, or enforce, effective regulations. A few examples are forests, and fisheries, but also carbon emissions. This review presents a selected number of results coming from field observations, laboratory experiments, and theoretical work, which pinpoint some of the more crucial aspects of these decision environments. Knowing which incentives and situational aspects may motivate resource users to adopt a more or less cooperative behavior can potentially be of pivotal importance to develop effective policies and regulations. At the same time, the research we present is also of great interestfor any diagnostic or explorative study that aims to study direct resource users, and their development of cooperative attitudes and practices.